PANDANGAN HUKUM ISLAM TERHADAP ADAT MOPOPENE’E DALAM PERKAWINAN SUKU LAUJE DI DESA LOMBOK KECAMATAN TINOMBO KABUPATEN PARIGI MOUTONG - Nuratika Nuratika; Muhammad Syarif Hasyim; Hamiyuddin Hamiyuddin (Familia: Jurnal Hukum Keluarga, 2020)
The implementation of adat in the Lauje community is aimed at upholding traditions that have been handed down as a symbol of honor and courtesy of the Lauje people in receiving guests. Then another goal in the implementation of this custom is to prevent the bride and groom's household from negative things that if this custom is not implemented. The purpose of this research is to describe and explain the implementation of the Mopopene’e custom system in the marriage of the Lauje tribe in the village of Lombok, Tinombo Subdistrict, Parigi Moutong Regency and how the objectives of Islamic law are towards the implementation of the Mopopene’e custom. This study uses qualitative methods and describes field research. In the technique of collecting data the author uses the method of observation and conduct interviews directly to the informant. The results of the study found that the implementation of the Mopopene'e custom which had been carried out by the Lauje people was a good tradition. As for the community's understanding of the adverse effects that will arise in the future if the custom is not implemented according to the author, it is only a myth that happens to happen and if it is not implemented it does not have any impact in the future because there is no power that exceeds the power of the creator, namely Allah swt.